2023
DOI: 10.1108/ecam-03-2022-0247
|View full text |Cite
|
Sign up to set email alerts
|

How cultural intelligence affects expatriate effectiveness in international construction projects

Abstract: PurposeThis study aims to investigate the influence mechanism of expatriates' cultural intelligence (CQ) on expatriate effectiveness (task performance and premature return intention), identifying work engagement as a mediator and cultural distance as a boundary condition.Design/methodology/approachDrawing on the conservation of resource theory and the person–environment fit (P–E fit) theory, a moderated mediation model is built. Working with a sample of 303 international construction expatriates collected by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Career Progression and Contributions: It is imperative to undertake an analysis of the effects of self-initiative expatriation on career advancement, development of skills, and prospects for future possibilities. Furthermore, the examination of the impacts made by these individuals on other entities such as companies, societies, and worldwide networks constitutes a substantial aspect (Chen et al, 2023). The assessment of organizational perceptions and support for self-initiative expatriates, as well as the examination of the wider societal ramifications of this phenomenon, represents a significant aspect of research (Singh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Career Progression and Contributions: It is imperative to undertake an analysis of the effects of self-initiative expatriation on career advancement, development of skills, and prospects for future possibilities. Furthermore, the examination of the impacts made by these individuals on other entities such as companies, societies, and worldwide networks constitutes a substantial aspect (Chen et al, 2023). The assessment of organizational perceptions and support for self-initiative expatriates, as well as the examination of the wider societal ramifications of this phenomenon, represents a significant aspect of research (Singh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the theory of cultural intelligence places significant emphasis on the capacity to effectively navigate and operate within environments characterized by cultural diversity. According to Chen et al (2023), expatriates who demonstrate self-initiative frequently demonstrate elevated levels of cultural intelligence, enabling them to effectively navigate and prosper in many cultural environments.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Likewise, some personal factors, i.e., career commitment, life satisfaction, and adaptation, also play a vital role in facilitating expatriate adjustment with cultural intelligence (Morin & Talbot, 2023). Moreover, this study uses a single moderator; it is suggested that future researchers test other moderating variables between the relationship of CQ and EA, i.e., leadership style, psychological contract, work-family satisfaction, knowledge sharing, and cross-culture adaptation (Chen et al, 2023;Morin & Talbot, 2023). Moreover, it would be interesting if future researchers find out the antecedents of CQ, i.e., personality traits and emotional stability (Morin & Talbot, 2023), or use CQ as a mediator or moderator, as research is scarce on CQ with these positions (Morin & Talbot, 2023).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In fact, cultural intelligence entails the ability to cooperatively use a set of skills to show certain qualities such as ambiguity tolerance and flexibility, which are appropriately based on values and attitudes. People's cultural values interact with others' 11 . Cultural intelligence enables individuals to act effectively in situations distinguished by cultural differences.…”
Section: Introductionmentioning
confidence: 99%